Sight Unseen - Rinehart, Mary Roberts, 1876-1958 (Salt Lake City, UT : Project Gutenberg, 1999)
"Sight Unseen" by Mary Roberts Rinehart is a novel likely written in the early 20th century. The story explores themes of psychical research and the deep intricacies of the human mind through the lens of a peculiar investigation into the death of Arthur Wells, conducted by a group referred to as the Neighborhood Club, comprised of neighbors and friends. The opening of the novel sets the stage for a mysterious investigation initiated by the Neighborhood Club, highlighting the allure and complexities of psychical phenomena. The narrator, a participant in these investigations, reflects on the group s recent séance involving a medium named Miss Jeremy, who appears to have made eerily accurate revelations about Arthur Wells's demise. The gathering of characters, including skeptical but engaged participants such as Sperry, the heart specialist, and Mrs. Dane, who acts as the gracious host, creates an atmosphere filled with tension and curiosity about the supernatural. As the narrative unfolds, the members of the club delve deeper into their inquiry, wrestling with both the psychological implications and the factual details surrounding Wells's tragic end, setting the stage for a rich blend of mystery and human emotion. (This is an automatically generated summary.)
Release date is 1999-11-01
Produced by An Anonymous Project Gutenberg Volunteer, and David Widger
Keywords: Fiction; Detective and mystery stories